500 Hz logon versus click ABR maturation - ÇİPRUT, AYŞE AYÇA (ELSEVIER IRELAND LTD, 2007)
Objectives: To provide age-equivalent norms for a 500 Hz logon evoked ABR obtained in a group of children ranging 40 weeks-4 years old and compare these 500 Hz tonal norms to age-equivalent norms for click-evoked ABR. Methods: Seventy-seven infants and children ranging from conceptional age of 40 weeks (term babies) to 4 years were tested with both click and tonal ABR without any risk factors for hearing loss. Results: Data analyses were consisted of 6 age groups. Mean wave V latencies were compared with the adult norms. Latencies were decreased by age in both click and tonal ABR recordings. Conclusion: Five hundred Hertz of tonal ABR wave V latency did not mature until to 2-4 years old but, click ABR wave V latency reached maturity at the same age range. (C) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: auditory brainstem response; click; tone burst stimuli (logon); BRAIN-STEM RESPONSE; POTENTIALS; THRESHOLD; BIRTH